Antenatal detection of an intraglossal ranula on ultrasound and magnetic resonance imaging - Cohen, Harris L.; Choudhri, Asim F.; Raju, Anand D.; Samson, Jacques; Mabry, Lisa M.; Thompson, Jerome W. (Journal of Pediatric Neuroradiology, 2014)
A lingual ranula is a rare cystic lesion of the tongue. Ranulas are typically sublingual mucoceles. We report perhaps the first lingual ranula identified in a fetus. It was identified by ultrasound and confirmed by magnetic resonance imaging. Knowledge of the presence of such a large intraoral mass antenatally allows diagnosis, monitoring, assessment of potential airway compromise and delivery planning. The possibility of impending airway compromise caused the planning of an ex-utero intrapartum treatment (EXIT) procedure performed at delivery. Identification of tongue tissue below a cystic intraoral mass suggests a lingual rather than a sublingual origin, a finding which helps stratify the differential diagnosis.
Keywords: Ranula; fetal; magnetic resonance; ultrasound; tongue